1992
DOI: 10.1002/mrm.1910240209
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet‐encoded MR imaging

Abstract: Wavelet encoding is presented and compared to phase encoding. In wavelet encoding a distribution of spins is excited by a slice selective RF pulse; for each repetition time the distribution excited has the profile of a wavelet at different scale and translation. The spin density can be reconstructed with an inverse wavelet transform. Wavelet encoding has three advantages over phase encoding: (1) there is no Gibb's ringing from partial volume effects, (2) the effective repetition time can be 36 times the repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 8 publications
1
68
0
Order By: Relevance
“…Rather than defining the transform matrix explicitly, it is much easier to describe the underlying decomposition algorithm, which uses the two complementary filters and . In the orthogonal case, the low-pass filter satisfies the so-called quadrature mirror filter (QMF) conditions (7) (8) where is the transfer function ( -transform) of . The high-pass filter is the modulated version of given by (9) The wavelet decomposition is implemented iteratively as in Fig.…”
Section: A Multiresolution and Wavelet Decomposition Of A One-dimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than defining the transform matrix explicitly, it is much easier to describe the underlying decomposition algorithm, which uses the two complementary filters and . In the orthogonal case, the low-pass filter satisfies the so-called quadrature mirror filter (QMF) conditions (7) (8) where is the transfer function ( -transform) of . The high-pass filter is the modulated version of given by (9) The wavelet decomposition is implemented iteratively as in Fig.…”
Section: A Multiresolution and Wavelet Decomposition Of A One-dimensmentioning
confidence: 99%
“…reconstruction [6], [7], and in the design of new acquisition schemes for magnetic resonance imaging (MRI) [8]- [11]. Wavelet representations are also well suited for a variety of data processing tasks.…”
mentioning
confidence: 99%
“…For example, instead of completing the k-space traversal for every measurement, accelerated MR data acquisition can be achieved by various alterations of the k-space trajectories and the associated image reconstruction algorithms, such as partial k-space sampling (10). Alternatively, a priori information-based methods can also improve the temporal resolution of MR dynamic measurements (11) with various implementations, such as keyhole imaging (12), singular value decomposition (SVD) MRI (13), and wavelet-encoded MRI (14). Rather than a direct measurement, it has been demonstrated that manipulating experimental design can obtain fMRI with millisecond temporal resolution (15).…”
mentioning
confidence: 99%
“…As such, the imaging equation is in the form of a Fourier integral. For notational convenience, we define here the dynamic imaging problem as the acquisition of a sequence of images, denoted as To overcome this problem, several data-sharing methods have been proposed for efficient dynamic imaging [1][2][3][4][5][6], two examples of which are the Keyhole and RIGR (Reduced-encoding Imaging by Generalized-series Reconstruction) techniques [1][2][3]. This paper presents an extension on the RIGR technique so that multiple references can be used to achieve high spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%